Analisis Zat Pengawet Boraks pada Cilok dan Pentol Bakso yang Dijual di Kabupaten Grobogan - Salma Ellya Sayidina; Wahyu Purwanjani; Estuningtyas Ayu Hapsari (Joseph: Journal of Science and Pharmacy, 2025)
Background: The increasing use of borax as an unauthorized preservative in foodssuch as cilok and pentol bakso sold in Grobogan Regency poses a threat to public health. Purpose: to examine the presence and concentration of borax in cilok and pentol bakso samples circulating in the area. Method: Qualitative analysis using boric acid test kits and quantitative analysis using Spectrophotometry UV-Vis to measure boric acid levels in the samples. Samples were collected from various street vendors, prepared and then analyzed in the laboratory. Results: The study results showed that borax was detected in one cilok sample with a the highest concentration reaching 112.22 μg/kg.  Conclusion: The study results indicate that some food vendors are still adding borax to their products. Therefore, further supervision and increased awareness regarding the risks of using borax in food are necessary.